Beyond bone biology: Lessons from team science. Issue 11 (22nd July 2020) - Zaidi, Mone; Lizneva, Daria; Gera, Sakshi; Taneja, Charit; Korkmaz, Funda; Gumerova, Anisa; Ievleva, Kseniia; Ahmad, Naseer; Ryu, Vitaly; Sun, Li; Kim, Se‐Min; New, Maria I.; et al.
Abstract: Today, research in biomedicine often requires the knowledge and technologies in diverse fields. Therefore, there is an increasing need for collaborative team science that crosses traditional disciplines. Here, we discuss our own lessons from both interdisciplinary and transdisciplinary teams, which ultimately ushered us to expand our research realm beyond bone biology.